2017
DOI: 10.1002/smll.201701275
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical 3D Cobalt‐Doped Fe3O4 Nanospheres@NG Hybrid as an Advanced Anode Material for High‐Performance Asymmetric Supercapacitors

Abstract: Hierarchical nanostructure, high electrical conductivity, extraordinary specific surface area, and unique porous architecture are essential properties in energy storage and conversion studies. A new type of hierarchical 3D cobalt encapsulated Fe O nanosphere is successfully developed on N-graphene sheet (Co-Fe O NS@NG) hybrid with unique nanostructure by simple, scalable, and efficient solvothermal technique. When applied as an electrode material for supercapacitors, hierarchical Co-Fe O NS@NG hybrid shows an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(40 citation statements)
references
References 59 publications
(83 reference statements)
2
35
0
Order By: Relevance
“…The spectrum of C 1s, as shown in Fig. 3(b), displays binding energies at 284.5, 285.6 and 286.8 eV, which are assigned to C-C, C-O and C O, respectively (Guo et al, 2017). The decreased intensity of the carbon binding to oxygen in the sample suggests that most oxygen-containing functional groups in layered graphene oxide have been reduced to RGO.…”
Section: Resultsmentioning
confidence: 98%
“…The spectrum of C 1s, as shown in Fig. 3(b), displays binding energies at 284.5, 285.6 and 286.8 eV, which are assigned to C-C, C-O and C O, respectively (Guo et al, 2017). The decreased intensity of the carbon binding to oxygen in the sample suggests that most oxygen-containing functional groups in layered graphene oxide have been reduced to RGO.…”
Section: Resultsmentioning
confidence: 98%
“…The NSC-Fe-2 showed outstanding capacitive behavior, and the specific capacity was 195 F g −1 at 1 A g −1 , as can be seen from Figure 6d. The symmetrical GCD curves at various current densities clearly demonstrate the ideal capacitive characteristic of NSC-Fe-2 [48]. Figure 6e displays the capacitance retention of NSC-Fe- x at different current densities.…”
Section: Resultsmentioning
confidence: 99%
“…It was proved that Fe 2 O 3 and CNT-GF are composited successfully. Guo et al [59] also analyzed the structure of Co-Fe 3 O 4 NS@NG (cobalt encapsulated Fe 3 O 4 nanosphere is developed on N-graphene sheet) by Raman spectroscopy. The Raman characteristic peak of Fe 3 O 4 (≈200-800 cm À1 ) showed that the complex was successfully synthesized.…”
Section: Electrical Double Layer Mechanismmentioning
confidence: 99%